2004
DOI: 10.1021/jp031197v
|View full text |Cite
|
Sign up to set email alerts
|

Saving Measurement Time in 13C NMR Spectroscopy

Abstract: An algorithm to produce acceptably accurate Fourier transform NMR spectra using many fewer transients than commonly obtained is introduced and applied to 13C chemical shift and one-dimensional INADEQUATE Lorentzian type spectra. The algorithm supplies criteria to recognize when to stop transient collection at a time too early for an acceptable spectrum to be produced by Fourier signal processing but not by harmonic inversion signal processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 15 publications
0
27
0
4
Order By: Relevance
“…(11)] analytically, we consider in this section a robust HI method [20,21], which allows us to fit an arbitrary potential function V(x) to a linear superposition of Gaussian functions…”
Section: Gaussian Approximation For the Potential Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…(11)] analytically, we consider in this section a robust HI method [20,21], which allows us to fit an arbitrary potential function V(x) to a linear superposition of Gaussian functions…”
Section: Gaussian Approximation For the Potential Functionmentioning
confidence: 99%
“…Singer showed that the usual LennardJones interaction can be fit to good approximation by the sum of two Gaussians. Using the harmonic inversion (HI) method [20,21], we fit the usual Lennard-Jones potential to the sum of two Gaussians. Below we show that the resulting deviations in the properties between the Lennard-Jones and resulting Gaussian fit systems are within acceptable limits.…”
Section: Introductionmentioning
confidence: 99%
“…In reference [1] (where the mathematics supporting this section is given), a signal processing scheme aimed at increasing the sensitivity of signal detection was introduced. Here, it is used to process weak 31 P and 17 O signals.…”
Section: Description Of the Methodologymentioning
confidence: 99%
“…Using the sample data available in the FID, a Hermitian correlation matrix is created [1]. The all-positive eigenvalues of this matrix are called the singular values.…”
Section: Description Of the Methodologymentioning
confidence: 99%
See 1 more Smart Citation